Pengaruh Mutasi Kerja dan Promosi Jabatan terhadap Semangat Kerja Karyawan di Bank BTN Syariah KC Tasikmalaya - Haikal Pirous; M. Ryzki Wiryawan; Mellani Diah Anggraeni (Jurnal Dimamu, 2021)
This study aims to determine how the effect of job transfers and promotions on employee morale at Bank BTN Syariah KC Tasikmalaya. The type of research is quantitative with an associative approach, the type of data is primary and uses data collection techniques in the form of observations, interviews, questionnaires and literature studies. The population in this study were employees of Bank BTN Syariah KC Tasikmalaya as many as 34 employees. The results of this study indicate that there is a significant effect between work mutations on employee morale at Bank BTN Syariah KC Tasikmalaya, the results of the t-test where tcount> ttable (5.675 > 2.039), there is no significant effect between job promotions on employee morale with the results of the t-test. where tcount < ttable (0.888 < 2.039), and simultaneously there is a significant effect between job transfer and promotion on employee morale with the results of the Ftest where Fcount > Ftable (15,615 > 3.29).